Garlic Bulb Decay and Soft Rot Caused by the Cross-Kingdom Pathogen Burkholderia gladioli - Abachi, Hamid (Plant disease, 2024)
In 2021, two gram-negative bacterial strains were isolated from garlic (Allium sativum) bulbs showing decay and soft rot symptoms in Central Iran. The bacterial strains were aggressively pathogenic on cactus, garlic, gladiolus, onion, potato, and saffron plants and induced soft rot symptoms on carrot, cucumber, potato, and radish discs. Furthermore, they were pathogenic on sporophores of cultivated and wild mushrooms. Phylogenetic analyses revealed that the bacterial strains belong to Burkholderia gladioli. Garlic bulb rot caused by B. gladioli has rarely been reported in the literature. Historically, B. gladioli strains had been assigned to four pathovars, namely, B. gladioli pv. alliicola, B. gladioli pv. gladioli, B. gladioli pv. agaricicola, and B. gladioli pv. cocovenenans, infecting onion, Gladiolus sp., and mushrooms and poisoning foods, respectively. Multilocus (i.e., 16S rRNA, atpD, gyrB, and lepA genes) sequence-based phylogenetic investigations including reference strains of B. gladioli pathovars showed that the two garlic strains belong to phylogenomic clade 2 of the species, which includes the pathotype strain of B. gladioli pv. alliicola. Although the garlic strains were phylogenetically closely related to the B. gladioli pv. alliicola reference strains, they possessed pathogenicity characteristics that overlapped with three of the four historical pathovars, including the ability to rot onion (pv. alliicola), gladiolus (pv. gladioli), and mushrooms (pv. agaricicola). Furthermore, the pathotype of each pathovar could infect the hosts of other pathovars, undermining the utility of the pathovar concept in this species. Overall, using phenotypic pathovar-oriented assays to classify B. gladioli strains should be replaced by phylogenetic or phylogenomic analysis